Implementasi Gerakan Edukatif Mahasiswa Dengan Sosialisasi Bijak Dan Kreatif Dalam Bersosial Media Di Desa Rawaapu Tahun 2023 - Achmad Zakaria; Kusmiyati Kusmiyati; Nur Cholis Majid (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by the government of a particular region. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. KKN-T was implemented in several villages, one of which was Rawaapu Village, Patimuan District, Cilacap Regency. The work program implemented is an individual work program in the form of wise and creative socialization in social media. Where the target is elementary school students/equivalent in Rawapu Village. With the hope that children in Rawaapu village can be wiser and more creative in using social media.